Analysis of Kiyai's Leadership in Developing the Quality of Islamic Boarding School Education - Yeni Suryani; Aan Hasanah; Dian Widiantari; Abdul Karim; Ahmad Zaldi; Jalaludin Jalaludin; Musa Musa (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study aims to analyze the kiyai leadership model in developing the quality of boarding school education. A qualitative approach with an interpretive paradigm was used in this study. A case study was designed at Pondok Pesantren Khas Kempek Cirebon during the year 2022-2023. Primary and secondary data were collected through observation, documentation, and interviews. After that, the data were analyzed, which included information reduction and data validation. The results of this study show that Kiyai implements a transformative leadership model in four dimensions, namely Idealized Influence, Intellectual Stimulation, Individual Consideration, Inspirational Motivation. Efforts made by the Kyai to improve the quality of education by making changes to the boarding school education system, namely with a directed and modern curriculum. The results of this study provide important insights for kyai in particular and for pesantren education managers in general about how to optimize their leadership to improve the quality of education being implemented by their pesantren institutions. This study also shows that a transformative leadership model of kiyai is needed in moving boarding school educational institutions to produce quality education.